PENYELESAIAN KERUGIAN KEUANGAN NEGARA - Henny Juliani (Faculty of Law, Universitas Diponegoro, 2010)
In order to implement governance and development to realize people prosperity, Government us bestowedauthority to manage public finance. The authority is classified as administrative authority and treasuryauthority. The authority on public finance management belonged to the government gives consequence toaccount on implementation of public finance management. Hence every behavior effecting public financeloss have to be accounted jurisdictionally. Those above mention undergird paper of ULegalAspect of Publicfinance Loss Solution